Factors associated with provision of mothers' own breast milk for Very Low Birth Weight (VLBW) infants on a South African tertiary care neonatal unit - Mutesu-Kapembwa, Kunda (Division of Neonatology, 2017)
Background: The maternal struggle to provide adequate breast milk for the infants' nutritional needs disadvantage preterm infants as the outcomes of those exclusively breast milk fed are superior to those fed infant formula. Objectives: To determine the proportion of Mothers' Own breast Milk (MOM) consumed by very low birth weight (VLBW) infants at Groote Schuur Hospital and explore potential maternal difficulties to provide MOM. Methods: In a prospective cross sectional study of 104 VLBW infant-mother dyads admitted between January and May 2015, an interviewer administered a structured questionnaire to the participating mothers before day 3 and on day 14. Infant folders were reviewed for gestational age, weight, and mode of delivery and the proportion of MOM received on days 1, 7 and 14 of life. Results: Ninety-one (88%) infants received <25% of enteral feeds as MOM on day 1. MOM made up >75% of enteral feeds in 60 infants (62%) on day 14 of life and 56(57.7%) received 100% as MOM. Infants with 2 or less siblings (22.2% vs 33.7% p=0.010) received a greater proportion MOM on day 14 as compared to those with larger families. 85.7% of the interviewed mothers would have preferred to stay in the hospital with their infants post discharge. Infant's weight, mode of delivery, maternal age, HIV status, hypertension, breastfeeding counselling, income, transport mode or distance from the hospital had no impact on MOM provision. Conclusion: Domestic responsibilities may affect mothers' breast milk provision to the newborn preterm. Breast-feeding counselling did not improve breast milk provision in this study. The effectiveness of current counselling methods may need to be examined and improved. Facilitating accommodation and rooming in of mother infant pairs from delivery to discharge may be useful in improving MOM provision to VLBW infants.